2018
DOI: 10.1080/15440478.2018.1434851
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of cellulosic fiber from red banana peduncle as reinforcement for potential applications

Abstract: Natural fiber-reinforced polymer composites (NRPCs) are replacing many synthetic fibers because of their cheap availability and their hygienic, ecological, biodegradable, and sustainable properties. This work involved extraction of new cellulosic fibers from red banana peduncle (RBP) plant and investigated its chemical composition, physical, structural, thermal, and tensile properties. RBP fibers (RBPFs) have high specific strength and good binding properties due to their light weight andpresence of high cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Ash wax content was determined using ASTM E 1755-01 method while the wax content was quantified using Conrad method. Moisture content was examined through an electron moisture analyzer (Sartorious, model MA45) and density in the raw and various treated AAFs was measured with the help of meltbertoledoxsz05 balance method [21,22]. In each treatment groups, five fiber samples were considered and average values are reported.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Ash wax content was determined using ASTM E 1755-01 method while the wax content was quantified using Conrad method. Moisture content was examined through an electron moisture analyzer (Sartorious, model MA45) and density in the raw and various treated AAFs was measured with the help of meltbertoledoxsz05 balance method [21,22]. In each treatment groups, five fiber samples were considered and average values are reported.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Higher surface to volume ratio of cellulose filler makes good contact surface with the resin which increase the surface reactivity and improves the bonding. 16 The fiber nature of the filler provides better properties that can align and orient with the matrix phase. Low structural defects also enhance the dimensional stability of the composites.…”
Section: Machinability Propertiesmentioning
confidence: 99%
“…14 Cellulose micro fibers extracted from various bio resources such as jute fibers, thespesia lampas plant, red banana peduncle plant, coir fibers were used as good reinforcement for improvement of the composite properties. 15–19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Several authors have reported on the suitability of natural fibers as reinforcements for composite production. [5][6][7][8] However, the natural fibers have some challenges when they are used as reinforcements in natural fiber-reinforced polymer composites, for they have low dimensional and thermal stability, high moisture uptake, and poor fiber-matrix adhesion. 1 These challenges can be overcome by physical and chemical treatments of the fibers and also modification of the matrix.…”
Section: Introductionmentioning
confidence: 99%